Origin and evolution of turiasaur dinosaurs set by means of a new 'rosetta' specimen from Spain. Issue 1 (3rd September 2020) - Royo-Torres, Rafael; Cobos, Alberto; Mocho, Pedro; Alcalá, Luis
Abstract: Turiasauria is a non-neosauropod eusauropod clade of dinosaurs known since 2006, when the description of Turiasaurus was published. This group, including Losillasaurus, was originally thought to have been restricted to the Late Jurassic of Spain. However, over the last decade, our knowledge of this group has improved with the discovery of new taxa such as Zby from the Portuguese Late Jurassic, Tendaguria from the Tanzanian Late Jurassic and Mierasaurus and Moabosaurus from the Early Cretaceous of the USA. Here, we describe a new specimen of Losillasaurus from Spain, which allows us to better understand the character variation in the cranial and postcranial skeleton. The review of some sauropod fauna of Madagascar, and inclusion of some specimens of Turiasauria, suggest that this clade might have arisen in the Middle Jurassic. According to our phylogenetic results, a specimen found in the early 19 th century in Madagascar is shown to be the oldest and only member of Turiasauria represented in the Middle Jurassic thus far. This is named Narindasaurus thevenini gen. & sp. nov. . Turiasauria is thus known from the Middle Jurassic in Pangaea, diversified in the Late Jurassic in Gondwana and Laurasia, and dispersed during the Early Cretaceous to North America.